'We are fighting a tide that keeps coming against us': a mixed method exploration of stressors in an English county police force. (15th January 2021) - Jackman, Patricia C.; Clay, Georgia; Coussens, Adam H.; Bird, Matthew D.; Henderson, Hannah
ABSTRACT: Against a backdrop of austerity, this mixed method paper provides a contemporary understanding of stressors in English policing by examining stressors experienced by police employees in the UK. In the first study, police officers ( n = 223) and police staff ( n = 134) in a county police force in England completed measures of operational and organisational stressors. Significantly higher scores were found for operational and organisational stressors in police officers compared to police staff. Police officers also reported higher operational and organisational stressor scores in comparison to norms for an international sample. In the second study, 27 police employees from the same force participated in focus groups exploring stressors in policing. The qualitative findings built on the first study by providing detailed insights into stressors presently experienced by police employees and the impact of police reform on stress. Implications of the findings and recommendations for future research are discussed.